A remark on the second neighborhood problem - Salman Ghazal (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2015)
Seymour's second neighborhood conjecture states that every simple digraph (without digons) has a vertex whose first out-neighborhood is at most as large as its second out-neighborhood. Such a vertex is said to have the second neighborhood property (SNP). We define